Prognostic value of the PrPC-ILK-IDO1 axis in the mesenchymal colorectal cancer subtype. (1st January 2021) - Ghazi, Alexandre; Le Corre, Delphine; Pilati, Camilla; Taieb, Julien; Aparicio, Thomas; Didelot, Audrey; Dedhar, Shoukat; Mulot, Claire; Le Malicot, Karine; Djouadi, Fatima; de Reynies, Aurélien; Launay, Jean-Marie; et al.
ABSTRACT: The CMS4 mesenchymal subtype of colorectal cancer (CRC) is associated with poor prognosis and resistance to treatment. The cellular prion protein PrP C is overexpressed in CMS4 tumors and controls the expression of a panel of CMS4-specific genes in CRC cell lines. Here, we sought to investigate PrP C downstream pathways that may underlie its role in CMS4 CRC. By combining gene set enrichment analyses and gain and loss of function approaches in CRC cell lines, we identify the integrin-linked kinase ILK as a proximal effector of PrP C that mediates its control on the CMS4 phenotype. We further leveraged three independent large CRC cohorts to assess correlations in gene expression pattern with patient outcomes and found that ILK is overexpressed in CMS4 mesenchymal tumors and confers a poor prognosis, especially when combined with high expression of the PrP C encoding gene PRNP . Of note, we discovered that the PrP C -ILK signaling axis controls the expression and activity of the tryptophan metabolizing enzyme indoleamine 2, 3 dioxygenase IDO1, a key player in immune tolerance. In addition, we monitored alterations in the levels of tryptophan and its metabolites of the kynurenine pathway in the plasma of metastatic CRC patients (n = 325) and we highlight their prognostic value in combination with plasma PrP C levels. Thus, the PrP C -ILK-IDO1 axis plays a key role in the mesenchymal subtype of CRC. PrP C and IDO1-targeted strategies may represent new avenues for patient stratification and treatment in CRC.